A New Scheme of Group-based AKA for Machine Type Communication over LTE Networks - Mariya Ouaissa; A. Rhattoy (Institute of Advanced Engineering and Science, 2018)
Machine Type Communication (MTC) is considered as one of the most important approaches to the future of mobile communication has attracted more and more attention. To reach the safety of MTC, applications in networks must meet the low power consumption requirements of devices and mass transmission device. When a large number of MTC devices get connected to the network, each MTC device must implement an independent access authentication process according to the 3GPP standard, which will cause serious traffic congestion in the Long Term Evolution (LTE) network. In this article, we propose a new group access authentication scheme, by which a huge number of MTC devices can be simultaneously authenticated by the network and establish an independent session key with the network respectively. Experimental results show that the proposed scheme can achieve robust security and avoid signaling overload on LTE networks